The Economic and Social Costs of Armed Conflict in El Salvador - Lopez, Humberto (World Bank, Washington, DC, 2012)
This note puts figures behind the notion of poverty resulting from war. Using simulation models, the author estimates the economic and social costs of the El Salvadorian conflict. The calculations suggest that had conflict been avoided, income per capita would have been almost the double of its actual value in 2002, the poverty rate lower by 15 percentage points, and Millenium Development Goals (MDG) indicators substantially better.